1991
DOI: 10.1016/s0025-6196(12)61170-7
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Thyroid Cancer Treated at the Mayo Clinic, 1946 Through 1970: Initial Manifestations, Pathologic Findings, Therapy, and Outcome

Abstract: We retrospectively analyzed the outcome of all patients who received their primary treatment for follicular thyroid cancer at the Mayo Clinic between 1946 and 1970. The diagnosis was confirmed by reexamination of preserved tissue specimens. The 57 female and 43 male patients (mean age, 53 years) underwent follow-up for a maximum of 32 years (mean, 17.4 years). All patients were treated surgically, and total removal of primary tumor was thought to have been accomplished in all but three. Only 2 of the 88 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
104
11
10

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(142 citation statements)
references
References 24 publications
17
104
11
10
Order By: Relevance
“…Tumor differentiation status was consistent with the results of other series. 9,34 The majority of cases diagnosed from 1973 to 1983 fell into was not reported for the majority of patients, and selective or variable reporting may have biased the surthis low-risk category with 10-year relative survival greater than 0.98. Patients with regional-or distantvival estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor differentiation status was consistent with the results of other series. 9,34 The majority of cases diagnosed from 1973 to 1983 fell into was not reported for the majority of patients, and selective or variable reporting may have biased the surthis low-risk category with 10-year relative survival greater than 0.98. Patients with regional-or distantvival estimates.…”
Section: Discussionmentioning
confidence: 99%
“…ICD-O ogy and stage. [9][10][11][12][13][14][15][16][17][18][19][20] However, the relative importance of each of these characteristics as prognostic factors and morphology codes were used to specify histologic types. 22 Papillary histology included codes 8050, 8260, whether findings in one population can be generalized to other populations is not known.…”
mentioning
confidence: 99%
“…Previous studies showed that widely invasive FTC displays a significantly poorer prognosis than minimally invasive FTC [4,5]. To date, other conventional prognostic factors of FTC such as distant metastasis at diagnosis (M1), old age, and large tumor size have also been identified [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, prognostic factors of minimally invasive FTC have not been intensively investigated and, to our knowledge, only one manuscript has been published for a large series of patients [23].…”
mentioning
confidence: 99%
“…Its lack of frequency has made it more difficult to study and often the results of papillary carcinoma have been extrapolated to follicular carcinoma (19,20,21). Very few studies have examined the risk factors affecting the prognosis of follicular carcinoma (19,20,21), and there is great variability between them. This could be a result of fewer patients in most studies, which means that small variations in the variables analyzed can lead to a prognostic factor being significant or not.…”
Section: Discussionmentioning
confidence: 99%